Explorando o relacionamento entre as medidas de desempenho na ALCOA Alumínio de Poços de Caldas. - Abreu, André Luís Trópia de (Universidade Federal de São Carlos, 2004)
The evolution of production organization models was observed with more intensity since the second half of the last century. Its purpose is to make organizations more competitive. A core element that accompanies this change is a performance measurement system with a more multidimensional framework in most organizations. The actors in this scenario use the information from these performance measurement systems for issues of planning, control and improvement. In this context, the relationship between performance measures has been providing information to each of these actors. The mental models of these actors are unique. Usually the formal model of relationship between the performance measures in use is not shared. The goal of this work is to research this problem and to evaluate how the sharing process occurs for the use of maps of relationships between performance measures. The main contribution is the creation and sharing of a model of relationships between performance measures among users of a performance measurement system. The evaluation of this sharing process took place for the application of some research tools in a quasi-experimental project.
Keywords: Processo decisório; Modelos de organização da produção; Modelos mentais; Medidas de desempenho; Mapas de relacionamento; Production Organization Models; Mental Models; Performance Measures; Relationship Maps; ENGENHARIAS::ENGENHARIA DE PRODUCAO